Budaya Kopi Dan Karakter Tempat: Telaah Genius Loci Pada Warung Kopi Purnama Di Bandung - Anita Viana; Agus S. Ekomadyo; Kurnia Widiastuti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Coffee Culture and Sense of Place: A Genius Loci Study of Warung Kopi Purnama in Bandung. This research examines the concept of genius loci or place intelligence to explain the uniqueness of a place, focusing on Warung Kopi Purnama in Bandung, established in 1930. The study explores how genius loci values shape the identity and distinct character of this historic coffee shop, which has preserved its secret recipes and original architectural features. Warung Kopi Purnama is portrayed as a place with strong emotional and historical identity, reflected in its classic architecture and old-world atmosphere. As a social space, it encourages direct interaction through a culture of conversation without internet access. Using qualitative descriptive methods through observation and interviews, the research identifies historical, religious, social, and cultural values embedded in the site. By analyzing image, place, character, and genius loci, the study reveals the meanings that contribute to Warung Kopi Purnama’s appeal. Its uniqueness is further emphasized by signature menus such as black iced coffee and sarikaya jam bread, as well as nostalgic architectural elements. Overall, Warung Kopi Purnama is seen as an entity with a soul and emotional identity, offering an authentic experience distinct from modern cafés.